Reform of Criminal Liability by Traffic Violators Resulting in Victim Fatality - Hendra Gunawan; Ade Saptomo (PT Publikasiku Academic Solution, 2024)
The purpose of this study is to analyze the system of criminal liability for traffic offenders resulting in fatalities and propose reforms to improve fairness and effectiveness in handling such cases. The study discusses the system of criminal liability for traffic offenders resulting in fatalities, and reforms that can be made to improve fairness and effectiveness in handling such cases. Through a review of existing regulations and an analysis of common issues in case handling, this study shows that the sanctions stipulated in the Road Traffic and Transportation Law (Law LLAJ) have not been able to provide an adequate deterrent effect for violators. In addition, inconsistent and unprofessional law enforcement also hampers the creation of an effective legal system. Therefore, reforms in the criminal liability system are necessary, including changes in the provision of more severe and strict sanctions, increased consistent law enforcement, and efforts to raise public awareness of the importance of compliance with traffic regulations.